2017
DOI: 10.1007/s11223-017-9872-6
|View full text |Cite
|
Sign up to set email alerts
|

Shear Behavior of Non-Persistent Joint Under High Normal Load

Abstract: â Ôàêóëüòåò ãðàaeäàíñêîãî ñòðîèòåëüñòâà, ÑÀÄÐÀ èíñòèòóò, Òåãåðàí, Èðàí ã Ñû÷óàíüñêèé óíèâåðñèòåò, ×ýíäó, Êèòàé Èññëåäîâàíî âëèÿíèå ðàçúåäèíåíèÿ ñîåäèíåíèÿ ïðè ñäâèãå ïëîñêîãî íåñòàáèëüíîãî ñîåäèíåíèÿ ïîä äåéñòâèåì èíòåíñèâíîé íîðìàëüíîé íàãðóçêè ñ èñïîëüçîâàíèåì ïðîãðàììíîãî îáåñïå÷åíèÿ PFC2D. Ïåðâîíà÷àëüíî êàëèáðîâêà PFC2D ïðîâåäåíà íà îñíîâå ýêñïåðèìåíòàëüíûõ äàííûõ äëÿ ñîãëàñîâàíèÿ ñ ìîäåëèðóåìûì ÷èñëîâûì ðåçóëüòàòîì. Äîñòîâåðíîñòü ìîäåëèðóåìûõ ìîäåëåé ïðîâåðåíà ïðè ñðàâíåíèè ñ ðåçóëüòàòàìè ïðÿìûõ èñïûòàíèé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In recent years, many scholars have used the discrete element method to simulate the propagation process of rock cracks, analyze the rock fracture mechanism, and verify the feasibility of this method for simulating rocks by comparing it with the laboratory experiment data [26][27][28][29]. In this section, CDEM was used to simulate a rock mass with prefabricated fractures under uniaxial compression.…”
Section: Feasibility Analysis Of Cdemmentioning
confidence: 99%
“…In recent years, many scholars have used the discrete element method to simulate the propagation process of rock cracks, analyze the rock fracture mechanism, and verify the feasibility of this method for simulating rocks by comparing it with the laboratory experiment data [26][27][28][29]. In this section, CDEM was used to simulate a rock mass with prefabricated fractures under uniaxial compression.…”
Section: Feasibility Analysis Of Cdemmentioning
confidence: 99%
“…The excavation stability in shaft sinking or tunnel and drifting engineering and bore-hole stability of oil and gas engineering are closely related to cavity-contained rock. Previously, a lot of attempts have been made to reveal the mechanical responses of cavity-contained rock by numerical test, 11,12 uniaxial or triaxal compression test, [13][14][15][16] multi-axis hollow column test, 17 Brazilian disk test, 18 uniaxial dynamic impacting test, [19][20][21] triaxial repetitive impact test, 22 and hydraulic fracturing test. 23 The strength, crack damage behavior, damage evolution, energy dissipation, hole spalling pattern, and failure modes were systemically investigated for hollow rock exposed to static to dynamic loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Haeri [28] studied the mechanism of crack propagation in concrete specimens containing cracks under shear loading conditions, and he found that the precracked concrete failure occurs in the mixed mode in the case of nonoverlapping cracks configuration and in the tensile mode for the overlapping cracks. Haeri [29][30][31][32] used a modified higher-order semi-infinite displacement discontinuity method (HSDDM) with thirdorder displacement discontinuity elements (cubic elements) to estimate the stress intensity factor in the fractured rocks underneath a single disc cutter. Yang et al [33,34] utilized DIC (digital image correlation) technology to monitor and analyze the failure process of specimens and investigated the relationship between the strength of the fractured rock and the crack propagation process.…”
Section: Introductionmentioning
confidence: 99%